ANALISIS SEJARAH PERUBAHAN UNDANG-UNDANG KESEHATAN DI INDONESIA: DAMPAK DAN IMPLIKASINYA - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Jurnal Kesehatan, 2025)
Health laws in Indonesia have undergone various changes throughout history to address the challenges of the times, community needs, and socio-political dynamics. This study analyses these changes, their impacts, and implications for the national health system. Regulatory improvements demonstrate the government's efforts to improve access to health services, strengthen service quality, and provide protection against public health threats. However, the implementation of these laws often faces obstacles such as infrastructure limitations, funding, and regional disparities. These changes also have significant social and economic implications, including improved quality of life, economic productivity, and strengthened investment in the health sector. This study highlights the importance of cross-sectoral collaboration and effective policy communication to ensure the sustainability of reforms, create an inclusive health system, and meet the needs of the community optimally.